Changes in nuclear permeability and histone distribution during herpesvirus infection - Salminen, Sami (2019)
Herpes simplex virus 1 (HSV-1) is a human pathogenic dsDNA virus capable of lytic orolabial infections in humans. Initial lytic infections lead to life-long and sporadically reactivating latent infections. In a lytic infection, viral DNA replication and progeny capsid assembly take place inside the host cell nucleus. The lytic infection results in extensive reorganization of nuclear structures and processes, including formation of viral replication compartments (VRCs) and marginalization of host chromatin to the nuclear periphery. Currently it is not known if these changes in nuclear architecture affect nucleocytoplasmic transport and nuclear permeability. Preliminary studies had indicated cytoplasmic histone accumulation during the infection, which could be due to changes in nuclear permeability. To study nucleocytoplasmic shuttling and localization of histones, confocal microscopy was used to analyze changes in histone distribution. Immunolabeling revealed an increase in the cytoplasmic localization of euchromatin (H3K27ac) marker and especially heterochromatin marker (H3K9me3) at 8 h and 12 h post infection (hpi). Fluorescence recovery after photobleaching (FRAP) experiments revealed a significant increase in the nuclear permeability of GFP at 12 hpi. Additionally, distribution of fluorescent importin β-EGFP shifted towards the nucleoplasm in infected cells at 8 and 12 hpi. These results suggest that marginalized chromatin does not hinder the nucleocytoplasmic shuttling of molecules and cytoplasmic accumulation of histones is not due to obstructed nuclear import. Instead, extranuclear histones and increase in nuclear permeability could be due to previously reported infection-induced nuclear pore impairment.